Batangas Brew a coffee production and wellness center - Malizon, Jeanette P. (College of Architecture, University of the Philippines Diliman, 2019)
Batangas is one of the main producers of coffee in the 19th century. With the pest infestation and coffee rust in the Philippine shores, it has caused the decline in coffee production in this area and has destroyed most of the coffee trees in Batangas. With the demand in the local consumption of coffee and our high dependency on importation, there is a need to revitalize the production and yield of coffee in the Philippines. Likewise, there is also a challenge for the local framers to produce globally competitive products that can be produced in large-scale while maintaining excellent quality and consistency. In order to challenge the feasibility of returning to the forefront of coffee production, the local coffee industry should overcome the following concerns : large-scale limitations, climate change and coffee diseases and agricultural land conversion and low produce value. This research aims to provide an architectural solution that would respond to the problems being faced by the coffee industry as well as highlight the sustainable use of coffee cherry. Specifically, the research will focus on the integration of three main concepts related to agriculture: wellness, innovation and production. Additionally, the research includes the possible wellness programs, possible innovations and technology, and the process of production that will be part of the development. These concepts were translated to spaces through the theories and the established programs: wellness programs and coffee production. The architectural design shows how these different programs for wellness and production and the required spaces relate to each other in terms of aesthetics and building connections. With this development, an integration of wellness and coffee production, a processing facility was provided to provide high quality plantlets. The facility also provided an administrative spaces for the Coffee Council in the municipality to oversee the flow of production producing globally competitive products consistent with quality and quantity, this effects the market value of the product making it possible for the farmers to have a higher income. For the wellness center, the facility has spaces for basic therapies. However, it is recommended that the use of coffee be maximized for its health and therapeutic use.